Metodologia de racionalização de gastos aplicada a órgãos públicos baseada na experiência da gestão de despesas do Governo do Estado do Ceará - Mendonça, Ocione Marques (2008)
The growth of government expenses that come along with increasing society demand for public service such as security, justice, education and health imposes to public officers to move toward management improvement aiming at reduce waste resources and get more value for money expended. The general objective of this work is to propose a rationalization expenses methodology applied to public sector that take into account its characteristics and legal specificities, making sustainable savings by expenses controls, purchase optimization, uniformity of controls, improvement of processes and augment of relationship with suppliers, replacing the customary fiscal adjustment without appropriate evaluation of savings perspectives and, principally, the impacts on society benefits. The study methodology is qualitative, exploratory, bibliography, documental and participative research once it took into account the author experience, and secondary data are the main source. The research result make possible to present a rationalization of expenses methodology applied to public sector, grouped in 6 (six) main phases and 17 (seventy) secondary phases. The study provides evidence that a rationalization of expenses methodology oriented to offer as main product the instruments for reaching sustainable savings is workable in public sector.